1989
DOI: 10.1007/bf00142049
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Trypanosoma congolense infection on the disposition kinetics of diminazene aceturate in the dog

Abstract: Diminazene aceturate was administered intravenously at 3.5 mg/kg body weight to mongrel dogs before and after infection with Trypanosoma congolense. Plasma and urine were collected at varying intervals thereafter and analysed for the compound. The mean area under the concentration-time curve (AUC) of diminazene in healthy dogs was 25.8 h.micrograms/ml but was significantly increased (p less than 0.05) to 35.7 h.micrograms/ml after infection with T. congolense. The distribution half-life was significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…More so, the curative effect of SEC-DA combination therapy in rats and dogs experimentally infected with T. b. brucei has been reported (Eke, 2016). Various studies on the kinetics of DA in different animal species have been reported (Kellner et al, 1985;Onyeyili & Anika, 1989;El Banna et al, 1999;Miller, 2005). Few reports on the tissue residues of DA in animals are available (Onyeyili, 1982;Gilbert, 1983;Kellner, 1985;Onyeyili & Anika, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…More so, the curative effect of SEC-DA combination therapy in rats and dogs experimentally infected with T. b. brucei has been reported (Eke, 2016). Various studies on the kinetics of DA in different animal species have been reported (Kellner et al, 1985;Onyeyili & Anika, 1989;El Banna et al, 1999;Miller, 2005). Few reports on the tissue residues of DA in animals are available (Onyeyili, 1982;Gilbert, 1983;Kellner, 1985;Onyeyili & Anika, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…(2009),Sumano et al (2004),Kikuvi et al (2001),Valladares et al (1998), Cullen et al (1998), Lloyd et al (1991,Gullichsen et al (1990),Anika and Onyeyili (1989),Onyeyili and Anika (1989),Romanosky et al (1983),Lu et al (1981) and McAfee et al . (2009a,b), Jensen et al (2006, 2004), Post et al (2002), Allaouchiche et al (2001), Lindecrona et al (2000), Agersø et al (1998), Monshouwer et al (1995), Moore et al (1995), Zeng and Fung (1990) and Vellenga et al (1992, 1989) Horse 43 4 Ensink et al (2005), Bucki et al (2004), Rees et al (1999) and Wichtel et al (1992) Cattle 126 14 TerHune et al (2005), Erskine et al (1995), Klein et al (2008), Litterio et al (2007), Washburn et al (2005),Kumar and Malik (1999a,b),Clarke et al (1996Clarke et al ( , 1993,Brown et al (1991b),Holland et al (1992),Mevius et al (1991) andClarke et al (1989) Variability in drug response 215…”
mentioning
confidence: 99%
“…However, the effect of a trypanosome infection on the pharmacokinetics of diminazene has been described only for rats (38), rabbits (19), and dogs (35). Since such information would have implications for the therapeutic regime used for cattle, the present study was conducted to determine whether the pharmacokinetics of diminazene in noninfected cattle differ significantly from those in cattle with an acute or chronic infection of T. congolense.…”
mentioning
confidence: 99%